A Web and SMS Gateway-Based Quality Monitoring Model of Upright Piano Painting - Kasino Kasino; Ahmad Juniar; Ridzky Kramanandita (Universitas Islam Sultan Agung, 2013)
This model of quality monitoring is a web and SMS gateway-based an application which is specifically designed for quality control of upright piano painting in PT XYZ. Previously, the data processing for preparing a daily report consume long time. The painting production always is evaluated every month due to wait collection daily reports for one month. This situation is very to be late and can damage the large number of painting. To overcome this problem, a web and SMS gateway-based quality monitoring model of Upright Piano Painting is designed. This model use evolutionary development algorithm, and based on Unified Modeling Language (UML). The result has indicated that the designed model can speed up the processing of daily data and send a SMS of daily monitoring report of quality upright piano painting to painting manager every day. So the evaluation of the production process can be conducted in daily period instead of monthly.